The Forgotten Second Quartile: Parental Income and Youth Post-Secondary Education Enrolment in Australia - Coelli, M (My University, 2010)
The relationship between parental income and the post-secondary education enrolment of youth aged 18-19 in Australia is investigated. Firstly, Census data from 1991 to 2006 are employed using the sample of youth still residing with parents. HILDA data are then used to analyze all youth over the 2004-2008 period, irrespective of living arrangements. The estimates highlight a strongly convex relationship for university enrolment, with enrolment rates essentially the same for the lowest two parental income quartiles, rising moderately for the third quartile then steeply for the top income quartile. This pattern is also observed if either parental occupation or postcode-based SES measures are employed rather than parental income. For other post-secondary enrolment, the relationship is an inverted U-shape. Parental education levels may have a large role in understanding these relationships.
University of Melbourne, Depatment of Economics Working Paper Series
Keywords: Education and Training; Education and Training -- Costs; Finance -- Expenditure and constraints on expenditure; Finance; Learning, education and training; Income, wealth and finances; Education and Training; Finance; Costs; Expenditure and constraints on expenditure; Learning, education and training; Income, wealth and finance